Two new species of Willowsia Shoebotham, 1917 (Collembola: Entomobryidae) from Arunachal Pradesh, India - Verma, Simran; Mandal, Guru Pada; Mandal, Pritha; Kar, Surajit (Zootaxa, 2026)
This study describes two new species, Willowsia coxichroma sp. nov. and Willowsia mitrai sp. nov., from the eastern part of the Indian Himalayas, specifically from one of the north-eastern states, namely Arunachal Pradesh. These two new species differ from the other members of Willowsia based on pigment pattern, scale type, and chaetotaxy. Molecular identification and genetic distance of Willowsia coxichroma sp. nov. with its congeners supported the novel species identity; however, the generation of barcodes was unsuccessful for Willowsia mitrai sp. nov. An updated key to Indian species of Willowsia and a comparison table of related species are also provided.